Breastfeeding and feeding practices in the first year of life and its association with overweight and obesity of children in Mexico - Armando Arredondo; Oscar Benjamin Reséndiz Lugo; Emanuel Orozco; Christian Paul Torres de la Rosa (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to evaluate feeding practices in the first year of life and their association with the development of overweight and obesity in children in Mexico. Methods: the association between overweight and obesity with different feeding practices were evaluated. The data was processed using the statistical package Stata version 14 using logistic regression models. Results: 396 children were evaluated; the prevalence of overweight and obesity was 6% and 7.7% presented a possible risk of overweight. 6.9% had exclusive breastfeeding in the first 6 months of life and 71.7% were fed infant formula. The variables significantly associated with the development of overweight and obesity in the first year of life were the age of the child (p =0.043, RR=0.57), the introduction of fluids in the first three days of life (p=0.02, RR=2.90), consumption of foods with a high sugar content (p =0.01, RR=0.25), consumption of milk other than breast (p =0.02, RR3.25) and egg consumption (p =0.05; RR=0.28). Conclusions: our results show that it is essential to attend complementary feeding practices and reinforce exclusive breastfeeding in the first year of life, as measures to prevent overweight and obesity to improve health in childhood.